ROLE OF HERBAL MEDICINES IN VITILIGO TREATMENT - CURRENT STATUS AND FUTURE PERSPECTIVES - Narayanaswamy, Radhakrishnan; Ismail, Intan Safinar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Vitiligo is a depigmentation disorder with complex causes. Nonetheless, recent progress has been made to unravel the pathophysiology of vitiligo. In this review, we provide an overview of the currently known herbal medicine for vitiligo treatment and also highlighted the herbs that have been used in clinical trials. In view of traditional uses, herbs such as Ammi visnaga L., Angelica sinensis, Eclipta alba L, Ginkgo biloba, Picrorhiza kurroa Royle Ex Benth, and Psoralea corylifolia L, have been highlighted. Enormous efforts in vitiligo drug discovery are currently needed. Interleukin-17 inhibition, tumor necrosis factor-alpha inhibition, heat shock protein-70i (HSP70i) inhibition, keratinocyte turnover modulators, and regulatory T cells (Tregs) modulators have been discussed as promising new targets for vitiligo drug development. Thus, we strongly believe that this review may be useful for rationalize new herbal drug for vitiligo treatment.